Valuation of Volkswagen AG - Gonçalves, Ricardo Emanuel Magalhães (2019)
VW AG represents one of the major empires of the automotive world. This agglomerate of 12 brands supplies to its clients, besides transportation vehicles, financial services of different nature. After the huge 2015 crisis, caused by the excessive CO2 gas emissions to the atmosphere, the whole group had the resilience and bravery to rebuild and come back to the top, constituting in 2017 the group of its sector with the highest amount of sales. Within the scope of the group activities, stands out a strong investment in the electric sector and reconciliation after the 2015 crisis, not only with the target clients, but also with the environment. Therefore, it is of enormous interest to evaluate not only the extension of the VW AG performance, but also to understand if all the panorama represents an investment opportunity at the stock market level, being performed for this purpose in this same document a whole group valuation. To do so, many tools such as the discounted cash flow model, the RVM or the DDM will be implemented. It is necessary to highlight that the different valuation models, due their different nature, also show different results. It is noteworthy that the dividend discounted model produced extremely different results from the other methods, because the dividends paid were also inconsistent, with abrupt changes over time. The combined result of the developed analysis shows that Volkswagen group shares were undervalued in the initial period of 2019, with a market value at the time of 136€ per share, which is different from those calculated using the valid methods applied on this analysis, whose aggregate average resulted in a value of € 153.32 per share.